The Impact of Mobility and Migration in the Roman Empire Proceedings of the Twelfth Workshop of the International Network Impact of Empire (Rome, June 17-19, 2015) - Lo Cascio, Elio; the assistance of Miriam Groen-Vallinga, with J. (Impact of Empire, 2016)
The Impact of Mobility and Migration in the Roman Empire assembles a series of papers on key themes of Roman mobility and migration, discussing i.a. the mobility of the army, of the elite, of women, and war-induced mobility and deportations. Readership: All interested in the history of migration and mobility, and anyone concerned with the social history of the Roman world. For the benefit of non-specialists all ancient sources are translated.